2015
DOI: 10.4067/s0718-16202015000300001
|View full text |Cite
|
Sign up to set email alerts
|

Gray mold caused by Botrytis cinerea limits grape production in Chile

Abstract: by Botrytis cinerea is a major disease of grapes (Vitis vinifera) that substantially reduces the yield and quality of grape production in temperate and humid regions of the world. B. cinerea is a necrotrophic fungus that attacks the non-lignified aerial organs of grapes; in particular, berries are highly susceptible during ripening. The polycyclic nature and exponential progress exhibited by GM at the beginning of the its epidemic, as well as the abundant inoculum production, the high dissemination efficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 184 publications
0
20
0
Order By: Relevance
“…This relationship between susceptibility and berry colour was expected because it has been shown that the susceptibility of grapes may be affected by the concentration of phenolic substances in grapes (Frankel et al 1995, Goldberg et al 1995, and particularly, the tannin concentration within the berry skin (Deytieux-Belleau et al 2009). Last, and in addition to fruit maturity, berry skin colour and bunch compactness, which also may affect the susceptibility to BBR, there are other predisposal factors, such as genetic (morphological, anatomical and chemical features of the berry skin), physical (wounds), environmental (climate and weather conditions) and agronomic (cultural practices) (Latorre et al 2015). In addition, the compactness of bunches has been shown to be an important morphological feature that affects the susceptibility to B. cinerea by affecting the microclimate and the thickness and wax content of the berry cuticle (Marois et al 1986, Vail and Marois 1991, Percival et al 1994, Fermaud et al 2001.…”
Section: Effect Of Grape Maturity On Disease Susceptibilitymentioning
confidence: 99%
See 3 more Smart Citations
“…This relationship between susceptibility and berry colour was expected because it has been shown that the susceptibility of grapes may be affected by the concentration of phenolic substances in grapes (Frankel et al 1995, Goldberg et al 1995, and particularly, the tannin concentration within the berry skin (Deytieux-Belleau et al 2009). Last, and in addition to fruit maturity, berry skin colour and bunch compactness, which also may affect the susceptibility to BBR, there are other predisposal factors, such as genetic (morphological, anatomical and chemical features of the berry skin), physical (wounds), environmental (climate and weather conditions) and agronomic (cultural practices) (Latorre et al 2015). In addition, the compactness of bunches has been shown to be an important morphological feature that affects the susceptibility to B. cinerea by affecting the microclimate and the thickness and wax content of the berry cuticle (Marois et al 1986, Vail and Marois 1991, Percival et al 1994, Fermaud et al 2001.…”
Section: Effect Of Grape Maturity On Disease Susceptibilitymentioning
confidence: 99%
“…This corroborates a previous study that showed a positive correlation between BBR development and bunch compactness (Hed et al 2009). Last, and in addition to fruit maturity, berry skin colour and bunch compactness, which also may affect the susceptibility to BBR, there are other predisposal factors, such as genetic (morphological, anatomical and chemical features of the berry skin), physical (wounds), environmental (climate and weather conditions) and agronomic (cultural practices) (Latorre et al 2015). For agronomic factors, after the climate influence, vegetative growth and canopy development are considered the second most important factors favouring B. cinerea development (Valdés-Gómez et al 2008).…”
Section: Effect Of Grape Maturity On Disease Susceptibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The control of tomato grey mould disease is commonly based on the application of synthetic fungicides. However, this approach is considered ineffective, due to the high capability of B. cinerea to develop fungicide resistance (Latorre, Elfar, & Ferrada, 2015;Rupp, Weber, Rieger, Detzel, & Hahn, 2017). In addition, the high application frequency in agricultural pest management programmes negatively impacts human health, food and the environment (Eyhorn, Roner, & Specking, 2015).…”
Section: Introductionmentioning
confidence: 99%